2009
DOI: 10.1007/s11033-009-9893-8
|View full text |Cite
|
Sign up to set email alerts
|

S-adenosylmethionine stimulates fatty acid metabolism-linked gene expression in porcine muscle satellite cells

Abstract: Evidence indicates that both S-adenosylmethionine (SAMe) metabolism and intramuscular fat are associated with insulin resistance and type II diabetes. However, it is still unknown whether SAMe have effects on intramuscular adipogenesis. The present study investigated the roles of SAMe in the adipogenic differentiation of porcine muscle satellite cells. Cells isolated from neonatal pig muscle were treated with different concentrations of SAMe (0, 0.5 and 1.0 mM) for 24 h, induced for a 9-day adipogenic differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Moreover, many genes and microRNAs were found to be involved in growth-related or lipid metabolism-related processes in other studies. For example, Zhang et al proved that myogenic regulatory factors (MRFs) were critical for successful myogenesis [ 8 ], and Yue et al demonstrated that adipocyte determination and differentiation factor-1 (ADD1) expression was related to adipocyte differentiation in pigs [ 9 ]. Besides, Feng et al found that microRNA-214 can influence skeletal muscle development by regulating embryonic myogenesis [ 10 ], and Li et al revealed that microRNA-103 had an impact on porcine preadipocyte differentiation through the putative target gene RAI14 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many genes and microRNAs were found to be involved in growth-related or lipid metabolism-related processes in other studies. For example, Zhang et al proved that myogenic regulatory factors (MRFs) were critical for successful myogenesis [ 8 ], and Yue et al demonstrated that adipocyte determination and differentiation factor-1 (ADD1) expression was related to adipocyte differentiation in pigs [ 9 ]. Besides, Feng et al found that microRNA-214 can influence skeletal muscle development by regulating embryonic myogenesis [ 10 ], and Li et al revealed that microRNA-103 had an impact on porcine preadipocyte differentiation through the putative target gene RAI14 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several coding genes associated with meat quality, for example adipocyte determination and differentiation dependent factor 1 (ADD1), which stimulates PPARgama expression and promotes adipogenic differentiation [48], whose expressional level is associated with IMF content (P < 0.05) [49]. The stearoyl-CoA desaturase (SCD) gene participates in fatty acids desaturation and oleic fatty acid synthesis, and SCD overexpression in muscle is correlated with a higher IMF content [50].…”
Section: Discussionmentioning
confidence: 99%
“…There are several coding genes associated with meat quality, such as adipocyte determination and differentiation dependent factor 1 (ADD1), which stimulates PPARgama expression and plays an important role in adipogenic differentiation [63], whose expressional level is positively correlated with IMF content (P < 0.05) [64], The stearoyl-CoA desaturase (SCD) gene plays a key role in the desaturation of fatty acids and synthesis of oleic fatty acid, and SCD overexpression in muscle is correlated with a higher IMF content [65]. SCD showed a signi cantly different expressional level in LD muscle between LT and LR pigs [66].…”
Section: Discussionmentioning
confidence: 99%